Enhanced coproduction of astaxanthin and lipids by the green microalga Chromochloris zofingiensis: Selected phytohormones as positive stimulators - Chen, Junhui; Wei, Dong; Lim, Phaik Eem (Elsevier, 2020)
Phytohormones comprise a variety of trace bioactive compounds that can stimulate cell growth and promote metabolic shifts. In the present work, a two-stage screening strategy was innovatively established to identify positive phytohormones for enhancement of astaxanthin and lipid coproduction in microplate-based cultures of mixotrophic Chromochloris zofingiensis. The results showed that auxins were the most efficient stimulators for astaxanthin accumulation. The maximum content of 13.1 mg/g and yield of 89.9 mg/L were obtained using indole propionic acid (10 mg/L) and indoleacetic acid (7.8 mg/L), representing the highest levels of astaxanthin in this microalga reported to date. Total lipids with the highest content (64.5% DW) and productivity (445.7 mg/L/d) were coproduced with astaxanthin using indoleacetic acid. Statistical analysis revealed close relations between phytohormones and astaxanthin and lipid biosynthesis. This study provides a novel original strategy for improving astaxanthin and lipid coproduction in C. zofingiensis using the selected phytohormones as positive stimulators. © 2019 Elsevier Ltd